Dynamics and Functional Interplay of Nonhistone Lysine Crotonylome and Ubiquitylome in Vascular Smooth Muscle Cell Phenotypic Remodeling - Cao, Shan-Hu; Chen, Zhi-Huan; Ma, Ru-Yuan; Yue, Lin; Jiang, Han-Mei; Dong, Li-Hua (Frontiers in Cardiovascular Medicine, 2022)
Background The crotonylation of histones is discovered of late as one of the post-translational modifications (PTMs) that can regulate gene expression. However, the function of crotonylation on nonhistone proteins in vascular smooth muscle cells (VSMCs) is unclear. Here, we aim to find the cellular characteristics of crotonylated nonhistone proteins and the cross talk with ubiquitinated proteins in VSMC phenotypic remodeling using the modified omics and proteomic analysis. Methods We performed the modified omics and proteomic analysis of VSMCs before and after the stimulation with platelet-derived growth factor-BB (PDGF-BB). The crotonylated and ubiquitinated pan-antibody was used to enrich proteins and then subjected to a high-throughput mass spectrometry analysis. The enrichment analysis was performed within differentially modified proteins in regard to GO terms, KEGG, and protein domains. Results As a result, there were 2,138 crotonylation sites in 534 proteins and 1,359 ubiquitination sites corresponding to 657 proteins. These crotonylated proteins detected after PDGF-BB stimulation might be involved in various vital cellular pathways and carry out important functions in VSMCs. Some of them closely took part in significant physiological processes of VSMC phenotypic remodeling, including glycolysis/gluconeogenesis, vascular smooth muscle contraction, and the PI3K-Akt signaling pathway. Furthermore, the KEGG pathway enrichment analysis showed the involvement of ubiquitinated proteins in the physiological processes of VSMC phenotypic remodeling, including glycolysis/gluconeogenesis, vascular smooth muscle contraction, RAS signaling pathway, or the PI3K-Akt signaling pathway. A cross talk analysis showed that there were 199 sites within the 177 proteins modified by crotonylation and ubiquitination simultaneously. Protein–protein interaction (PPI) network analysis indicated that crotonylated and ubiquitinated proteins play an important role in cellular bioprocess commonly and possibly have a synergistic effect. Conclusion In summary, our bioinformatics analysis shows that the crotonylation and ubiquitination of nonhistone proteins play an essential role in VSMC phenotypic transformation induced by PDGF-BB stimulation. The cross talk between crotonylation and ubiquitination in glycolysis is possibly a novel mechanism during VSMC phenotypic remodeling.